eIF3a Regulates Colorectal Cancer Metastasis via Translational Activation of RhoA and Cdc42 - Mei, Chao; Liu, Chong; Gao, Ying; Dai, Wen-Ting; Zhang, Wei; Li, Xi; Liu, Zhao-Qian (Frontiers in Cell and Developmental Biology, 2022)
Tumor metastasis is the major cause of tumor relapse and cancer-associated mortality in colorectal cancer, leading to poor therapeutic responses and reduced survival. eIF3a was previously described as an oncogene. However, its role in colorectal cancer progression and metastasis has not yet been fully investigated. In this study, the expression specificity and predictive value of eIF3a were investigated in clinical samples. The effects of eIF3a on cell proliferation and migration were verified in vivo and in vitro, respectively. The underlying molecular mechanism was revealed by western blotting, immunofluorescence, RNA-binding protein immunoprecipitation, and dual-luciferase reporter gene assays. The results showed that eIF3a was significantly overexpressed in tumor tissues compared with adjacent normal tissues. High eIF3a expression was correlated with tumor metastasis and overall survival. Downregulation of eIF3a obviously inhibited the proliferation and motility of malignant cells in vitro and in vivo. Mechanistically, eIF3a regulates Cdc42 and RhoA expression at the translation level, which further affects pseudopodia formation and actin cytoskeleton remodeling. Taken together, eIF3a accelerates the acquisition of the migratory phenotype of cancer cells by activating Cdc42 and RhoA expression at the translational level. Our study identified eIF3a as a promising target for inhibiting colorectal cancer metastasis.